The effect of the efflux pump inhibitor Carbonyl Cyanide m-Chlorophenylhydrazone (CCCP) on the susceptibility to imipenem and cefepime in clinical strains of Acinetobacter baumannii. - Alejandra Sanchez-Carbonel; Belén Mondragón; Nicolás López-Chegne; Isaac Peña-Tuesta; Gladys Huayan-Dávila; Dora Blitchtein; Hugo Carrillo-Ng; Wilmer Silva-Caso; Miguel Angel Aguilar-Luis; Juana Del Valle-Mendoza (PLoS ONE)
Introduction In the last years the rapid expansion of multidrug-resistant A. baumannii strains have become a major health problem. Efflux pumps are a group of transport proteins that contribute to the development of antibiotic resistance. The aim of this study was to evaluate the effect of the efflux pump inhibitor carbonyl cyanide 3-chlorophenylhydrazone (CCCP) on the antimicrobial action of imipenem and cefepime on clinical strains of A. baumannii. Materials and methods A total of 49 non-duplicate clinical samples were collected during January through December of 2018 from patients hospitalized in the Hospital Regional Docente de Cajamarca. Of the 49 samples obtained, the confirmatory identification of A. baumannii was performed on 47 samples by molecular methods. The amplification of the blaOXA-51-like gene was carried out by polymerase chain reaction (PCR). The determination of the minimum inhibitory concentration (MIC) was calculated using the microdilution method in culture broth. The susceptibility to both antibiotics (cefepime and imipenem) was evaluated in the presence and absence of the inhibitor carbonyl cyanide 3-chlorophenylhydrazone (CCCP). Results A total of 47 strains of A. baumannii were isolated: 97.87% (46/47) were resistant to Imipenem, 2.13% (1/47) of them were classified as intermediate and none of these strains were susceptible. On the other hand, 51.06% (24/47) of isolates were resistant to cefepime; 19.15% (9/47) intermediate and 29.79% (14/47) susceptible. We considered a significant difference in antibiotic susceptibility if the MIC changed at least 4 dilutions, after the addition of the inhibitor. In the case of CCCP in addition to imipenem, 2.1% (1/47) had a significant change of 4 or more reductions in MIC, 59.6% (28/47) achieved a change equal or less than 3 dilutions and 17.0% (8/47) did not have any change. In the case of CCCP with cefepime the percentage of strains with the significant change of MIC was 8.5% (4/47). On the other hand, 53.2% (24/47) presented a reduction equal or less than 3 dilutions and 12.8% (6/47) did not show changes. Conclusion In conclusion, our results demonstrate that the use of CCCP may improve the antibiotic effect of imipenem and cefepime on clinical strains of A. baumannii. The relevance of this study is that it provides evidence that this efflux pump inhibitor may be an alternative treatment against multidrug-resistant A. baumannii.